PHOTOBOOK DESIGN ABOUT FOODCOURT IN BATAM CITY - Hendi Sama; Nelson Tan (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Batam City is one of the cities that has become a tourist destination for local residents and foreign tourists. As the largest city in the Riau island, Batam City has a wide variety of foods from various regions. One of the uniqueness of Batam city is the foodcourt which provides many food stands, from breakfast to dinner all available at the foodcourt. The amount of food available in the food court in Batam city makes it difficult for the writer to decide what to eat for this photobook. Photobooks are print media that contain photos and are arranged in the form of a book. Photobooks can be used as a medium to convey messages about information on the topic to be discussed. The purpose of this research is to introduce and promote food and also the foodcourt in Batam City. The data collection technique used was interview and location observation at the foodcourt. The application used by the author to design the photobook is Adobe Photoshop CC 2017 and the final result in this research is a photobook containing food, food stands, and a food court. The results of the photobook will be printed with a size of 20 x 20cm. The results of the photobook will be printed with a size of 20 x 20cm. With this photobook, it is hoped that the foodcourt will be more attractive to potential buyers, both local residents and foreign tourists, and add insight to the existing foodcourts in Batam City, according to the results of the Research & Development analysis that has been carried out.